What if… I Asked Cancer Patients About Psychological Distress? Barriers in Psycho-Oncological Screening From the Perspective of Nurses–A Qualitative Analysis - Dreismann, Lara; Goretzki, Alina; Ginger, Viktoria; Zimmermann, Tanja (Frontiers in Psychiatry, 2022)
Introduction: Screening questionnaires to assess psychological distress in cancer patients are well established, but in practice there are difficulties in implementation screening up to referral to psycho-oncology. Interdisciplinary collaboration between psycho-oncology, physicians, and nursing is very important to this process. However, there are barriers and obstacles on all sides. Objective: The aim of this study is to capture in particular the barriers from the perspective of oncology nursing. Materials and Methods: Semi-structured interviews with nursing experts (n = 15; n = 10 female; 24-62 years) from different oncology departments of three university hospitals in Germanys were conducted and qualitative content analysis was carried out by two raters. Results: The Screening routine is variably well integrated into daily clinical practice. Structural barriers such as time pressure and a lack of focus on mental distress in nursing are present. Barriers on the side of nurses are primarily a lack of knowledge and communication insecurities when dealing with patients. Conclusions: There is a need for training and implementation of a disciplinary screening approach. The structural and organizational barriers, which are a challenge for the successful screening process due to unfavorable interdisciplinary team communication and clinical daily structure, should be addressed in further studies. Implications for Practice: In order to establish an interdisciplinary screening process and to overcome the barriers, trainings to deal with knowledge deficits and insecurities seem to be useful.